2015
DOI: 10.2337/db15-0546
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NOX-Derived Superoxide Exacerbates Diabetogenic CD4 T-Cell Effector Responses in Type 1 Diabetes

Abstract: Reactive oxygen species (ROS) play prominent roles in numerous biological systems. While classically expressed by neutrophils and macrophages, CD4 T cells also express NADPH oxidase (NOX), the superoxide-generating multisubunit enzyme. Our laboratory recently demonstrated that superoxide-deficient nonobese diabetic (NOD.Ncf1m1J) mice exhibited a delay in type 1 diabetes (T1D) partially due to blunted IFN-γ synthesis by CD4 T cells. For further investigation of the roles of superoxide on CD4 T-cell diabetogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
(85 reference statements)
1
18
1
Order By: Relevance
“…Here, we demonstrated that LPS/IL-4 treatment increased anti-inflammatory markers in NOX2 −/− BMDMs when compared to WT BMDMs. Unexpectedly, we observed no genotype-related change in STAT6 activation, which conflicts with a prior report showing that pSTAT6 expression is enhanced in NOX2 −/− BMDMs [44]. Such discrepancies may be due to the different activation stimuli employed in each study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, we demonstrated that LPS/IL-4 treatment increased anti-inflammatory markers in NOX2 −/− BMDMs when compared to WT BMDMs. Unexpectedly, we observed no genotype-related change in STAT6 activation, which conflicts with a prior report showing that pSTAT6 expression is enhanced in NOX2 −/− BMDMs [44]. Such discrepancies may be due to the different activation stimuli employed in each study.…”
Section: Discussioncontrasting
confidence: 99%
“…In our model, the mixed LPS/IL-4 stimulus significantly increased pSTAT1 expression in WT and NOX2 −/− BMDMs, but STAT1 activation was significantly reduced in NOX2 −/− BMDMs. This is in agreement with a previous report where NOX deficient macrophages incubated in the presence of IFNγ/LPS exhibited decreased STAT1 activation [44]. In addition, previous work demonstrated that LPS-induced IFNβ is required for STAT1 activation [45], and this may be a mechanism that explains reduced pSTAT1 and decreased pro-inflammatory marker expression in NOX2 −/− BMDMs.…”
Section: Discussionsupporting
confidence: 93%
“…As pro-inflammatory chemokine synthesis is redox-regulated [41] and (PVPON/TA) nanothin multilayer coatings can function as an antioxidant to dissipate free radicals (Figure 1 and [7]), the ability of (PVPON/TA) n to regulate pro-inflammatory chemokines implicated in islet transplant rejection within p(I:C)-stimulated BM-M ϕ was examined by qRT-PCR and ELISA. Expression of CCL5 and CXCL10 mRNA accumulation and protein expression by qRT-PCR and ELISA, respectively, was significantly lowered when p(I:C)-stimulated samples were treated with (PVPON/TA) n capsules (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Chemokine expression was measured in the supernatants of stimulated macrophages for 72 hours as described [41]. Pro-inflammatory CCL5 and CXCL10 chemokines were detected with DuoSet ELISA kit and antibody pairs (R&D Systems) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, although NOD mice are normally resistant to EAE, 91 they display strong disease in the absence of Ncf1. Moreover, by using Ncf1 m1J mutated mice 51 harboring a single autoreactive T‐cell clone from a NOD mouse ( BDC‐2.5.Ncf1 m1J ), 92 a reduced Treg suppressive capacity became apparent, inducing diabetes during both spontaneous and adoptive transfer of T1D 93 . Also, an increased production of pro‐inflammatory cytokines, like TNF‐α, IL‐17A and IFN‐γ is detected by BDC‐2.5.Ncf1 m1J cells in vitro confirming the contribution of both T H 1 and T H 17 to T1D pathology.…”
Section: Type I Diabetesmentioning
confidence: 99%